Using Taxol-sensitized budding yeast to investigate the effect of microtubule stabilization on anaphase onset - Angela R. Bunning; Samuel J. Anderson; Mohan L. Gupta, Jr. (STAR Protocols, 2023)
Summary: The microtubule (MT)-stabilizing drug Taxol (paclitaxel) is a commonly used tool to investigate MT dynamics and MT-dependent processes. Here, we present a protocol for using Taxol-sensitized budding yeast to investigate the effect of microtubule stabilization on anaphase onset. We describe steps for establishing a log phase culture, synchronizing cells in G1, arresting in metaphase, and releasing cells into Taxol. We then detail procedures for imaging and scoring anaphase onset. This protocol facilitates maintenance and reproducibility in testing drug-sensitized and Taxol-sensitized yeast strains.For complete details on the use and execution of this protocol, please refer to Proudfoot et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.